Physical Properties of Semiconducting/Magnetic Nanocomposites - Granitzer, Petra; Rumpf, Klemens (Frontiers in Materials, 2015)
In this review the fabrication of porous silicon/magnetic nanocomposite materials and their physical properties are elucidated. Especially the investigation of the presented systems with respect to their magnetic properties is reported. Furthermore the influence of the semiconducting matrix on the properties of the nanocomposites is highlighted. The main focus will be put on silicon used as template-material. In general the nanocomposite systems are fabricated in a two-step process, first by anodization of a silicon wafer to achieve porous silicon structures, and second by electrodeposition of a magnetic material into the pores. The morphology of the porous silicon template offers straight pores, grown perpendicular to the wafer surface. The magnetic nanostructures deposited within the pores lead to specific properties of the composite dependent on their size and shape. Due to their mutual arrangement magnetic coupling between these structures can occur whereas, coupling between adjacent pores depends on the porous silicon morphology. In a first section different types of such template/metal systems are reviewed and second an experimental part follows implying the porous silicon formation as well as the subsequent metal deposition process. Third the magnetic and optical properties of the systems are described. In a forth chapter the influence of the semiconducting matrix on these properties is elucidated and finally some prospects and conclusions are addressed.